2006
DOI: 10.1021/cc060041c
|View full text |Cite
|
Sign up to set email alerts
|

A Combinatorial Approach to the Study of Particle Size Effects on Supported Electrocatalysts: Oxygen Reduction on Gold

Abstract: A novel high-throughput technique has been developed for the investigation of the influence of supported metal particle size and the support on electrocatalytic activity. Arrays with a gradation of catalyst particle sizes are fabricated in a physical vapor deposition system that also allows selection of the support material. Simultaneous electrochemical measurements at all electrodes in the array, together with determination of the actual particle size distribution on each of the electrodes by transmission ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
103
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 86 publications
(111 citation statements)
references
References 36 publications
(48 reference statements)
7
103
0
Order By: Relevance
“…Combinatorial chemistry would allow the simultaneous synthesis and screening of a large number of alloys under identical conditions relevant to the aluminiumeair environment. This technique is growing in popularity to optimise the composition of materials having specific physical or chemical properties [147]. Using this technology, a 10 Â 10 array of individually addressable aluminium alloy electrodes could be fabricated onto a silicon nitride capped silicon wafer in a high-throughput physical vapour deposition system.…”
Section: Identification Of New Aluminium Alloy Anodes Via Combinatorimentioning
confidence: 99%
See 2 more Smart Citations
“…Combinatorial chemistry would allow the simultaneous synthesis and screening of a large number of alloys under identical conditions relevant to the aluminiumeair environment. This technique is growing in popularity to optimise the composition of materials having specific physical or chemical properties [147]. Using this technology, a 10 Â 10 array of individually addressable aluminium alloy electrodes could be fabricated onto a silicon nitride capped silicon wafer in a high-throughput physical vapour deposition system.…”
Section: Identification Of New Aluminium Alloy Anodes Via Combinatorimentioning
confidence: 99%
“…Using this technology, a 10 Â 10 array of individually addressable aluminium alloy electrodes could be fabricated onto a silicon nitride capped silicon wafer in a high-throughput physical vapour deposition system. The array would contain a gradient of varying aluminium alloy composition [147,148].…”
Section: Identification Of New Aluminium Alloy Anodes Via Combinatorimentioning
confidence: 99%
See 1 more Smart Citation
“…12 Following characterization of the particle size distributions, the activity of the supported catalysts was evaluated using silicon micro-fabricated arrays of 100 electrodes. 13 Of particular interest has been the effect of the support material and the particle size on the activity of the electrocatalysts. We have so far focused our attention on supported gold particles, and indeed recently demonstrated that there is a strong substrate and particle size effect for the electrooxidation of carbon monoxide on reduced titania (TiO x ) supported gold.…”
Section: Introductionmentioning
confidence: 99%
“…Each jetted ink droplet has a known composition and by controlling the number of droplets from the different inks, arrays of catalyst spots with gradient compositions can easily be prepared. After post-processing, the catalytically most active composition can be identified by using different screening methods including fluorescence, [17] employing electrode arrays, [18,19] scanning electrochemical microscopy [20,21] and electrochemical scanning droplet cells. [22] Inkjet printed electrocatalyst libraries were reported first by Reddington et al who printed Pt, Ru, Os and Ir based halide salts.…”
Section: Inkjet Printing Of Electrocatalystsmentioning
confidence: 99%